THE IMPACT OF GROUP-TO-GROUP EXCHANGE (GGE) METHOD IN GRAMMAR LEARNING - Alamsyah, Ade Nauval (English Edu: Journal of English Teaching and Learning, 2025)
This study rigorously examines the pedagogical efficacy of the Group-to-Group Exchange (GGE) method in enhancing grammar acquisition among a cohort of twenty-eightth-grade students at a junior high school in Banyuwangi, Indonesia. Employing a concurrent mixed-methods design, quantitative data were gathered via standardized classroom observations—measuring Johnson andJohnson’s five cooperative-learning elements—and pre- and post-test grammar assessmentsdeveloped from the official school syllabus and cross-checked against CEFR rubrics by subjectteachers. Qualitative insights were derived from semi-structured interviews with both students andtheir instructors. Over an eight-week intervention, observation scores averaged 4.20 on a 5-point Likert scale (promotive interaction M = 4.50; social skills M = 4.25), indicating high levels ofcollaborative engagement. Paired-sample t-tests revealed a statistically significant improvement in grammar proficiency (pre-test M = 50.50 vs. post-test M = 69.25; Δ = +18.75, SD = 7.76, t(19) = –10.81, p < .001), with a large effect size (Cohen’s d ≈ 2.41). Interview themes highlightedincreased motivation, peer-supported scaffolding, and positive shifts in classroom dynamics, alongside challenges such as passive participation and vocabulary constraints. Triangulation ofthese data sources confirms that GGE not only promotes syntactic mastery but also cultivatesmetacognitive awareness and learner autonomy. The findings advocate for the strategic integrationof GGE within EFL curricula, recommending structured cross-group rotations, facilitator training, and targeted vocabulary supports to optimize cooperative grammar instruction in contexts similarto Indonesian secondary schools.